Debating Residential Demand Charges and Time‐of‐Use Rates. Issue 9 (25th March 2018) - Chapman, Bruce; O'Sheasy, Michael
Abstract : Traditionally, residential electric customers of most utilities have been served under rates that have emphasized simplicity.